Pengaruh Mobile Customer Relationship Management Pada Bidang Perbankan - Elika Thea Kirana; Made Sandra Intan Giri Khrismayanti (Query: Journal of Information Systems, 2018)
Currently, Customer Relationship Management underwent a paradigm shift from a single channel relationship (organizational-to-customer relationship) to multi channels of relationships (customer-organization-organization customer- machines) with an emphasis on integration and collaboration. The relatively recent development of Information and Communication Technology, particularly in smartphones and big data applications, has been a key driver of this paradigm shift. Mobile Customer Relationship Management (mCRM) system is one of the latest advances in this CRM system. Mobile CRM promotes customer satisfaction through mobile media, especially in banking. In the context of mCRM, the presence of m-banking applications, contributes to improving and maintaining customer satisfaction and loyalty. This study aims to determine whether the use of mobile banking is an easy and effective way as a strategic tool mobile CRM system to communicate with customers. This research uses quantitative research approach and literature study from previous research. A self-administered questionnaire using Likert scale was developed and tested. The results prove that the use of mBanking on mCRM is an effective strategy that will improve customer satisfaction and improve the level of trust and customer satisfaction through the provision of mobile communications marketing services better. Keywords: mobile banking, customer relationship management, mobile CRM